PERANAN ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SMPN 7 SAMPIT - Siti Halimah; Mahmu’ddin Mahmu’ddin; Lulu Nazmi Al Idrus (STKIP MUHAMMADIYAH SAMPIT, 2019)
The role of parents can determine the success of children in addition to the motivation to learn that each child has. This study was conducted to determine the differences of teacher performance having certification and not. The population in this study is all students of class VIII SMP Negeri 7 Sampit with 83 students. Data analysis techniques used are techniques of regression analysis simple. The results of the analysis showed there is a role of parents in improving student learning motivation in SMPN 7 Sampit in the academic year of 2017.